Mental Disorder and Criminal Law - Schopp, R. (2017)
The death penalty has long played a central role in jurisprudence, in terms of identifying the most serious offenses and the most culpable offenders, as well as understanding the mental conditions that may exclude an offender from such a sentence. More recently, the debate has intensified on competency to face [execution], the effects of psychological impairment on that competency, and the role of expert witnesses in establishing criminal culpability. The edited volume, Mental Disorder and Criminal Law authoritatively blends empirical findings and legal expertise with sophisticated reasoning and ethical analysis to promote a deeper understanding of these complex issues at the interface of legal and psychological domains. In short, it explores the concept of (as termed by one chapter author) "protecting well-being while pursuing justice."